Peningkatan Nilai Tambah melalui Pelatihan Teknik Pengolahan dan Pengemasan Bayam di Komunitas Petani Sayur - Ayu Dian Pratiwi Permatahati; Astri Shabrina; Sa’idy; Dwi Riana (Wisanggeni: Jurnal Pengabdian Masyarakat, 2023)
Abstract The spinach farmer community in the partner area still faces challenges in increasing the added value of agricultural products due to limited knowledge of processing and packaging techniques. This community service activity aims to enhance farmers' understanding of the importance of sorting, grading, and packaging as initial steps toward improving product quality and marketability. The implementation method used the Asset-Based Community Development (ABCD) approach, focusing on leveraging local assets and active community participation during the training. The activity was conducted in a one-day technical session involving practical packaging demonstrations and discussions, without product simulation. The results showed a significant improvement in participants’ understanding of post-harvest quality principles and a new awareness of economic opportunities through value-added processing. The ABCD approach proved effective in uncovering local potential and fostering sustainable and independent social transformation.